Analysis of the impact of development tools used on the performance of the mobile application - Kotarski, Paweł; Śledź, Kacper; Smołka, Jakub (Journal of Computer Sciences Institute, 2018)
Solutions that allow developers to create application for different mobile systems in which they can share whole source code or large parts of it are becoming more popular. This article compares the performance of Android-based mobile application created with the default and multiplatform tools. Authors on selected examples examine performance in various aspects of the application.